2023
DOI: 10.3390/medicina59020323
|View full text |Cite
|
Sign up to set email alerts
|

Salubrinal Ameliorates Inflammation and Neovascularization via the Caspase 3/Enos Signaling in an Alkaline-Induced Rat Corneal Neovascularization Model

Abstract: Background and Objectives: Ocular alkaline burn is a clinical emergency that can cause permanent vision loss due to limbal stem cell deficiency and corneal neovascularization (CNV). Although the basic pathogenetic mechanisms are considered to be acute oxidative stress and corneal neovascularization triggered by inflammation, the underlying intracellular mechanisms have not been clearly elucidated. The aim of this study was to investigate the role of endoplasmic reticulum (ER) stress on inflammation and neovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…8 Inhibiting ER stress mitigates DES [9][10][11] and protects against alkaline burn induced corneal injuries. 12,13 One of our previous studies confirmed excessive ER stress (marked by a higher level of XBP1 and CHOP expression) in the process of corneal wound healing in diabetes; specifically, inhibiting ER stress with 4-phenylbutyric acid (4-PBA) significantly accelerates corneal epithelial and nerve regeneration. 14 Although the primary downstream mechanisms are considered to be excessive inflammation and programmed cell death triggered by ER stress, the underlying molecular mechanism of ER stress affecting corneal epithelial and nerve repair have not been elucidated.…”
mentioning
confidence: 84%
“…8 Inhibiting ER stress mitigates DES [9][10][11] and protects against alkaline burn induced corneal injuries. 12,13 One of our previous studies confirmed excessive ER stress (marked by a higher level of XBP1 and CHOP expression) in the process of corneal wound healing in diabetes; specifically, inhibiting ER stress with 4-phenylbutyric acid (4-PBA) significantly accelerates corneal epithelial and nerve regeneration. 14 Although the primary downstream mechanisms are considered to be excessive inflammation and programmed cell death triggered by ER stress, the underlying molecular mechanism of ER stress affecting corneal epithelial and nerve repair have not been elucidated.…”
mentioning
confidence: 84%
“…Clinically, corneal alkali burns (CAB) can lead to a range of complications such as delayed epithelial healing, conjunctival scar formation, dry eye disease, vascularization and corneal clouding [ 177 ]. The major pathological features following CAB are corneal vascularization, inflammation, and fibrosis [ 178 , 179 ]. Several studies have shown that rapamycin, a mTOR receptor inhibitor, can reduce corneal turbidity and neovascularization in CAB by various signaling pathways like TGF-1/ERK [ 180 , 181 ].…”
Section: Methylation In Cdsmentioning
confidence: 99%
“…ER stress can induce nucleotide-binding domain and leucine-rich repeat containing (NLRP3) inflammasome through PERK and IRElα pathways, regulate the release of inflammatory cytokines, and trigger inflammatory response [ 196 ]. Wang et al [ 197 ] demonstrated that there is a positive feedback loop between interleukin-17A (IL-17A) and ER stress, and that inhibition of ER stress or IL-17A can reduce the neovascularization area of DR. At present, inhibition of ER stress can alleviate inflammation and inhibit angiogenesis, which has been proved in both cell and animal experiments [ 186 , 198 ]. Although ER stress pathway shows great potential in anti-inflammatory and anti-vascular therapy, more in-depth mechanism studies are needed before clinical trials.…”
Section: Effects Of Er Stress Pathways On Angiogenesismentioning
confidence: 99%